Robustness of the Drosophila segment polarity network to transient perturbations. - Subramanian, K.; Gadgil, C. (IET Systems Biology, 2010)
Continuous and Boolean models for the Drosophila segment polarity network have shown that the system is able to maintain the wild-type pattern when subjected to sustained changes in the interaction parameters and initial conditions. Embryo development is likely to occur under fluctuating environmental conditions. Here, a well-established Boolean model is used to explore the ability of the segment polarity network to resist transient changes. Paths along which alternate unviable states are reached, and hence critical nodes whose state changes lead the system away from the wild-type state, are identified. It is found that the system appears to be more sensitive to changes that involve activation of normally inactive nodes. Through a simulation of the heat shock response, it is shown how a localised perturbation in one parasegment is more deleterious than a global perturbation affecting all parasegments. The sequence of events involved in the recovery of the system from a global transient heat shock condition is identified. Finally, these results are discussed in terms of the robustness of the system response.